Effect of PbO on the elastic behavior of ZnOP2O5 glass systems - Abd. Aziz, Sidek; El-Mallawany, R.; Matori, Khamirul Amin; Mohamed Kamari, Halimah (Elsevier, 2016)
A series of ternary phosphate glasses in the form of 40(P2O5)–(60 − x)ZnO–xPbO and 50(P2O5)–(50 − x)ZnO–xPbO where x = 0–60 mol%, have been successfully prepared by conventional melt quenching technique. Both longitudinal and shear ultrasonic velocities were measured in different compositions of PbO using the MBS8000 ultrasonic data acquisition system at 10 MHz frequency and at room temperature. The ultrasonic velocity data, the density and the calculated elastic moduli are found to be composition dependent and discussed in terms of PbO modifiers. The correlation of elastic moduli with the atomic packing density of these glasses was discussed. To predict the compositional dependence of elastic moduli of this glass system, the interpretation of the variation in the experimental elastic behavior observed has been studied based on various of the bond compression and the Makishima–Mackenzie models.